ACTIVITY PARTICIPATION AND STUDENT PROFILES IN A GEN Z UNIVERSITY - Andry Manodotua Panjaitan; Agustina Christiani; Natalia Hartono; Evanglin Millenia Lumempow (Polyglot, 2021)
Human resources are an important factor in the industrial world because they help innovate, create, and lead (soft skills). The industrial sector in the future will be dominated by Generation Z individuals, most of whom are currently university students. Therefore, it is very important for students to develop their soft skills. One way for students to develop soft skills is by participating in student activities. Based on research conducted at Universitas Pelita Harapan, results show that 22% of students are not actively participating in student activities. The aim of this research was to find and analyze the correlation between student profiles, namely the student's home faculty/academic major, class, and gender, with inactive participation in student activities. This study also analyzes the reasons for and considerations of student inactivity based on the characteristics of Generation Z and provides suggestions for student activities desired by students. Data was collected using a questionnaire filled out by 1214 respondents and interviews, then processed using SPSS software version 25.  The results of the data processing show that there is a correlation between student profiles, namely faculty/academic major and class, with the inactivity of students participating in student activities (p-value <0.05) and there is not a sufficient correlation between gender and student inactivity in student activities (p-value > 0.05). There are several reasons and considerations that cause students not to actively participate in student activities which are then used as suggestions for new student activities.BAHASA INDONESIA ABSTRACT: Sumber Daya Manusia merupakan salah satu aset penting dalam dunia Industri karena memiliki kemampuan untuk berinovasi, berkreasi dan memimpin (soft skill). Angkatan kerja pada era industri ini akan diisi oleh para individu generasi Z, sebagian besar adalah mahasiswa perguruan tinggi. Oleh sebab itu sangat penting bagi mahasiswa untuk mengembangkan softskill mereka. Salah satu cara mengembangkan softskill pada mahasiswa adalah dengan mengikuti kegiatan kemahasiswaan. Berdasarkan penelitian yang dilakukan di Universitas Pelita Harapan, diketahui bahwa terdapat 22% mahasiswa yang tidak aktif mengikuti kegiatan kemahasiswaan. Penelitian ini dilakukan di Universitas Pelita Harapan, dengan tujuan untuk mengetahui dan menganalisis hubungan antara profil mahasiswa, yaitu fakultas asal mahasiswa, angkatan, dan jenis kelamin dengan ketidakaktifan dalam mengikuti kegiatan kemahasiswaan. Lalu, untuk menganalisis alasan dan pertimbangan ketidakaktifan mahasiswa dihubungkan dengan karakteristik generasi Z berdasarkan teori yang ada, serta memberikan usulan dan saran kegiatan kemahasiswaan bagi UPH. Pengumpulan data dilakukan dengan kuesioner dan wawancara, kemudian diolah dengan software SPSS. Hasil pengolahan data menunjukan bahwa terdapat hubungan antara profil mahasiswa yaitu fakultas dan angkatan dengan ketidakaktifan mahasiswa dalam mengikuti kegiatan kemahasiswaan (p-value <0,05) dan tidak terdapat hubungan antara jenis kelamin dengan ketidakaktifan mahasiswa dalam mengikuti kegiatan kemahasiswaan (p-value >0,05). Terdapat beberapa alasan dan pertimbanagan yang menyebabkan mahasiswa tidak aktif mengikuti kegiatan kemahasiswaan. Setelah itu, usulan dan saran dapat dilakukan analisis lebih lanjut mengenai jenis kegiatan yang paling sesuai untuk dilaksanakan, berdasarkan profil mahasiswa yang berbeda-beda.